A survey of antimalarial drug use practices among urban dwellers in Abeokuta, Nigeria (2010)
Drug-use pattern of anti-malarial has been associated with development of resistant strain and therapeutic failure. This descriptive cross-sectional study was carried out to assess anti-malarial drug-use practices among dwellers of Adigbe communities within Abeokuta environment. The study documented the knowledge, the attitude and behaviour of three hundred and fifty (350) respondents in terms of drug preference, attitude to drug use and the effects of non-compliance to antimalarial drug. Structured questionnaires were used for data collection, as total of 370 questionnaires were distributed and 350 questionnaires were retrieved for analysis. One hundred and twenty five (125) (35.71) of the respondents frequently experienced malaria attack and practiced self-medication. One hundred and fifteen (115) (32.86%) of the respondents treated their malaria episode with Sulphadoxine-Pyrimethamine (SP) combination while 90 (25.71%) of the respondents frequently purchased Artesunate as monotherapy for malaria treatment due to cost-implication of the newer and available Artemisinin combination therapy (ACT’s). The finding reveals that 43 (12.29%) of the respondents only purchased Artemisinin-Combination Therapy (ACTs). One hundred and eight can 118 (33.71%) of the respondents practiced self-medication with anti-malarial drug. The results revealed therapeutic failure to conventional use of Sulphadoxine-Pyrimethamine (SP) by the respondents as One hundred and thirty nine (139) (33.71%) of the respondents experienced no cure and have to repeat the treatment with anti-malarias. If drug-use pattern of anti-malarials is not monitored, there is possibility of early emergence of resistance to the highly effective anti-malarial drugs presently in use.